Identifying Ionic and Electronic Charge Transfer at Oxide Heterointerfaces. Issue 4 (2nd December 2020) - Rose, Marc‐André; Šmíd, Břetislav; Vorokhta, Mykhailo; Slipukhina, Ivetta; Andrä, Michael; Bluhm, Hendrik; Duchoň, Tomáš; Ležaić, Marjana; Chambers, Scott A.; Dittmann, Regina; Mueller, David N.; Gunkel, Felix
Abstract: The ability to tailor oxide heterointerfaces has led to novel properties in low‐dimensional oxide systems. A fundamental understanding of these properties is based on the concept of electronic charge transfer. However, the electronic properties of oxide heterointerfaces crucially depend on their ionic constitution and defect structure: ionic charges contribute to charge transfer and screening at oxide interfaces, triggering a thermodynamic balance of ionic and electronic structures. Quantitative understanding of the electronic and ionic roles regarding charge‐transfer phenomena poses a central challenge. Here, the electronic and ionic structure is simultaneously investigated at the prototypical charge‐transfer heterointerface, LaAlO3 /SrTiO3 . Applying in situ photoemission spectroscopy under oxygen ambient, ionic and electronic charge transfer is deconvoluted in response to the oxygen atmosphere at elevated temperatures. In this way, both the rich and variable chemistry of complex oxides and the associated electronic properties are equally embraced. The interfacial electron gas is depleted through an ionic rearrangement in the strontium cation sublattice when oxygen is applied, resulting in an inverse and reversible balance between cation vacancies and electrons, while the mobility of ionic species is found to be considerably enhanced as compared to the bulk. Triggered by these ionic phenomena, the electronic transport and magnetic signature of the heterointerface are significantly altered. Abstract : The combined role of ionic and electronic charge transfer in oxide heterointerfaces (LaAlO3 /SrTiO3 ) is investigated. New near‐ambient‐pressure X‐ray photoelectron spectroscopy data proves a reversible Sr cation reconstruction under thermodynamic treatment to be responsible for lowered interface conductivity and enhanced magnetism under low temperatures. Ionic movement is found to be considerably higher and more influential than in the bulk.